CONTRIBUTIONS TO MODELING OF 4D FRACTALS - Babače, Elena; Kocić, Ljubiša (Matematichki Bilten, 2009)
Affine invariant IFS’s (AIFS) are Iterated Function Systems whose affine transformations are based on areal coordinates with respect to a certain simplex. In this note, we consider 4-dimensional generalizations of some classic and non-classic fractal objects generated by such AIFS and show how it can be used for modeling purposes. The stress is put on the one of the most desirable properties in modeling, according to CAGD specialists, convex hull property.